(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Cirrhosis is the terminal stage of fibrosis of liver parenchyma which leads to hepatic function alteration and formations of regenerating nodules. Our Study aimed to study NLR and its correlation with Child Turcotte Pugh score in patients with liver cirrhosis. Material and Method: Our hospital based cross sectional study was conducted among the patients with liver cirrhosis of age more than 18 years attending medicine OP and IP of Aarupadai Veedu Medical College and Hospital. After getting written and informed consent patient’s blood was collected for assessment of complete blood count by Five-part Haematology analyser, Liver function Tests by Photometry and Ultrasonography of abdomen was done. From this NLR was derived and the severity of liver cirrhosis was graded using Child Turcotte Pugh score. Statistical data were documented and analysed using SPSS v21 operating on windows 10. Results: In present study total of 150 patients fulfilling inclusion criteria are included with mean age of 50.89±10.41yrs of age. On classifying the liver disease, 48% of patients were with CTP class B, followed with 45.3% CTP class C and 6.7% with CTP class A. Neutrophil-Lymphocyte Ratio (NLR) ratio was significantly higher among the CTP Class C (4.99±2.08) compared to class B (3.18±1.10) and class A (2.57±0.87) in decreasing order, with p<0.05. there is significant positive strength of association of NLR with severity of the liver disease with higher CTP score and class of severity (r=0.602, p<0.05). Conclusion: Neutrophil-to-lymphocyte ratio (NLR) is a novel inflammation index. As emerging laboratory marker, NLR could be used as accurate prognostic marker to predict severity of the inflammatory process. There is significant positive strength of correlation of NLR with the Child Turcotte Pugh score in patients with liver cirrhosis. So NLR can be used as biomarker to predict the stage of liver cirrhosis and its outcome.